Youth Participation in Village Development in Imbanagara Village, Ciamis District, Ciamis Regency - Mel Asni Gustiani; Otong Husni Taufiq; R. Rindu Garvera (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
This study discusses the level of youth involvement in village development in Imbanagara Village, Ciamis District, Ciamis Regency. The research used a descriptive qualitative approach with a focus on the four dimensions of participation according to Cohen and Uphoff, namely decision making, implementation, receipt of benefits, and evaluation. The results showed that youth participation is still not optimal, as seen from the low participation in deliberation forums, the minimal role in the implementation of development activities, as well as limitations in experiencing benefits and involvement in the evaluation process. Obstacles found include the lack of youth awareness of their strategic role, apathy, and the lack of guidance and communication from the village government. Efforts that have been made include coaching through Karang Taruna, strengthening coordination between youth and village government, and adjusting the timing of activities so that they do not clash with the youth's busy schedules. This study recommends the importance of sustainable strategies to increase youth awareness and capacity in participatory village development.